Using neural nets for reducing gas concentrations by the data of trass gas analyzer at CO2-laser; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 5 - Kataev M. Yu. (Control, computer engineeringand information science, 2007)
Заглавие с титульного листа